2018
DOI: 10.1017/s0960258518000260
|View full text |Cite
|
Sign up to set email alerts
|

A response of the imbibed dormant red rice caryopsis to biotic challenges involves extracellular pH increase to elicit superoxide production

Abstract: Seeds often survive in the soil in a dormant state, but their persistence is endangered by micro-organisms that could feed on them. Seed–microbe interactions in the soil are, however, poorly understood. We used dormant caryopses of red rice to study the defence response induced by pronase, a mixture of proteases secreted by Streptomyces griseus, a non-pathogenic bacterium. Pronase was shown to activate the plant immune reaction, indicating that its activity was recognized as a potential microbial attack. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
(154 reference statements)
0
2
0
Order By: Relevance
“…This is a physical-chemical defence, necessarily arrayed on the exterior of the seed, that favours long-term persistence in the soil [ 38 ]. In red rice, a red-grained, weedy type of rice whose spikelets (caryopses covered by the hull) can persist dormant in the soil for one or more years, accumulation of PAs and PA-associated compounds seems to be an important defence strategy providing protection against biotic challenges [ 41 ]. Skadhauge et al [ 10 ] also observed a moderate effect of extracts of PAs-accumulating barley testa layers on Fusurium growth, and concluded that the PAs and catechin in the testa layer of the mature barley grain are part of a passive resistance mechanism, acting as a physical barrier against pathogen attack.…”
Section: Resultsmentioning
confidence: 99%
“…This is a physical-chemical defence, necessarily arrayed on the exterior of the seed, that favours long-term persistence in the soil [ 38 ]. In red rice, a red-grained, weedy type of rice whose spikelets (caryopses covered by the hull) can persist dormant in the soil for one or more years, accumulation of PAs and PA-associated compounds seems to be an important defence strategy providing protection against biotic challenges [ 41 ]. Skadhauge et al [ 10 ] also observed a moderate effect of extracts of PAs-accumulating barley testa layers on Fusurium growth, and concluded that the PAs and catechin in the testa layer of the mature barley grain are part of a passive resistance mechanism, acting as a physical barrier against pathogen attack.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, ROS that interact with wall polysaccharides and promote cell elongation in germinating seeds are produced in the cell walls of growing embryos at the time of radicle protrusion. ROS also have an important role in defence against attacks by challenging microorganisms [188,189].…”
Section: Ros No and The Emergency Gearmentioning
confidence: 99%
“…Wheat ( Triticum aestivum L.) is the third most significant cereal in the world (Horvath et al ., 2009; Clifton and Keogh, 2018; Ghotbzadeh and Gianinetti, 2018; Wulff and Dhugga, 2018). The higher level of ploidy and the complexity of the hexaploid wheat genome have increased its physiological and ecological flexibility in comparison with the tetraploid and diploid ancestors (Dubcovsky and Dvorak, 2007; Feldman et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%